Low-metallicity Nova Explosions: A Site for Weak rp-process Nucleosynthesis - Athanasios Psaltis; Jordi José; Richard Longland; Christian Iliadis (The Astrophysical Journal, 2025)
Classical novae are common cataclysmic events involving a binary system of a white dwarf and a main-sequence or red giant companion star. In metal-poor environments, these explosions produce ejecta differently from their solar counterparts due to the accretion of subsolar-metallicity material onto the white dwarf. In particular, it has been suggested that the nucleosynthesis flow in such low-metallicity nova explosions extends up to the Cu–Zn region, much beyond the expected endpoint, around Ca, predicted for solar-metallicity classical novae. This behavior resembles a weak rp -process, and such nuclear activity has never been observed in accreting white dwarf binaries with typical accretion flows. In this work, we study the characteristics of the weak rp -process for four nova models with metallicities Z = 2 × 10 ^−9 , 10 ^−7 , 2 × 10 ^−6 , and 2 × 10 ^−5 , and explore the impact of the nuclear physics uncertainties via a Monte Carlo sensitivity study. We identify nuclear reactions whose uncertainties affect the production of intermediate-mass nuclei under these conditions. These reactions and relevant nuclear quantities are targets for measurements at stable or radioactive beam facilities to reduce their rate uncertainties.